PRINCIPLES OF PROFESSIONAL COMPETENCY IMPROVEMENT IN FUTURE TECHNOLOGICAL EDUCATION TEACHERS THROUGH DESIGN PROCEDURE - Makhbuba Aslanovna Khalmukhamedova (Web of Journals Publishing, 2024)
The article discusses the principles of increasing the professional competence of future teachers of technological education of students with the help of the Naqshbandi heritage.
Keywords: competence, professional competence, educational qualifications of professional competence, pedagogical program of individual development, self-development, teacher's work on himself, stages of the teacher’s work on himself, self-esteem, heritage, mysticism, outlandishness, religious values.